Acute obstructive pyelonephritis: prognosis of inflammatory response regression - I. E. Mamaev; G. Sh. Saypulaev; K. A. Dolomanov; A. I. Tolmacheva; S. V. Kotov (Вестник урологии, 2024)
Introduction. Predicting the timing of inflammation control in acute obstructive pyelonephritis based on routine laboratory values is of great importance. This is essential for planning the next stage of management to eliminate the cause of obstruction.Objective. To evaluate the dynamics and prognostic value of systemic inflammatory response markers in the management of acute obstructive pyelonephritis (AOP).Materials & methods. We performed a prospective study of the dynamics of inflammatory markers in patients with AOP. The study included 113 patients with AOP. Nephrostomy tube was installed in 43 and ureteral stent in 70. Following parameters were assessed: leukocytosis, CRP, creatinine on the days 1-3-7 after drainage, duration of fever. The risk factors for long-term regression of leukocytosis were also investigated.Results. On post-op day 3, the average leukocytosis was 10.5 (± 2.46) *109, and 68.1% of patients are returned to normal leukocyte level, and on post-op day 7 — 7.9 (± 3.12) *109 and 75.2%, respectively. On post-op day 3, the average CRP level was 14.2 (± 63.95) mg/l, and 32.7% of patients had decrease to target values, on post-op day 7 — 13.1 (± 49.7) mg/l and 56.6%, respectively. On post-op day 6, fever resolved in 98% of patients. Diabetes mellitus was the only statistically significant factor that can influence the long persistence of leukocytosis (p < 0.05).Conclusion. Leukocytosis showed higher specificity as a marker of inflammatory regression than CRP for AOP treatment. On post-op day 7, 75% of patients demonstrated laboratory and clinical signs for the inflammatory process relief. The presence of diabetes mellitus significantly prolongs the regression of the inflammatory response.